2015
DOI: 10.1017/s1751731115000944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wheat dried distillers grains and enzyme supplementation on growth rates, feed conversion ratio and beef fatty acid profile in feedlot steers

Abstract: The objectives of this study were to determine: (1) the effect of wheat dried distillers grain with solubles (DDGS) inclusion, and (2) dietary feed enzyme (FE; Econase XT) supplementation in a finishing diet containing wheat DDGS on fatty acid profile of the pars costalis diaphragmatis muscle of beef cattle. A total of 160 crossbred yearling steers with initial BW of 495 ± 38 kg were blocked by BW and randomized into 16 pens (10 head/pen). The pens were randomly assigned to one of the four treatments: (1) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(38 reference statements)
0
5
0
1
Order By: Relevance
“…The removal of the starch fraction of corn during distillers grains production can increase the protein and lipid content of DDGS to be three times more concentrated compared with corn ( Srichuwong and Jane, 2011 ). Thus, DDGS can significantly alter the fatty acid composition of feeds due to the increase in corn oil concentration ( Li et al, 2012 ; Wang et al, 2012 ; He et al, 2015 ). The primary fatty acid found in DDGS is linoleic acid (C18:2) ( Ruan et al, 2018 ), and previous literature has concluded feeding a diet containing high levels of DDGS can alter the fatty acid profile in meat from various livestock species, with particular focus on the increase of C18:2 ( Brandt et al, 1992 ; Gill et al, 2008 ; de Mello et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The removal of the starch fraction of corn during distillers grains production can increase the protein and lipid content of DDGS to be three times more concentrated compared with corn ( Srichuwong and Jane, 2011 ). Thus, DDGS can significantly alter the fatty acid composition of feeds due to the increase in corn oil concentration ( Li et al, 2012 ; Wang et al, 2012 ; He et al, 2015 ). The primary fatty acid found in DDGS is linoleic acid (C18:2) ( Ruan et al, 2018 ), and previous literature has concluded feeding a diet containing high levels of DDGS can alter the fatty acid profile in meat from various livestock species, with particular focus on the increase of C18:2 ( Brandt et al, 1992 ; Gill et al, 2008 ; de Mello et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dugan et al (2007) demonstrated backfat from steers fed a barley grain‐based diet had on average more t 10‐ than t 11‐18:1, but individual animal variation was such that some animals had more t 11‐18:1. In addition, even though the majority of studies feeding barley grain‐based diets result in the trans ‐10 shift, at least one (He et al, 2015) did not, and in this study, substituting wheat DDGS for barley gain did not lead to further improvements in the t ‐18:1 isomer profile (Table 2). Perhaps a slight change in barley starch content, availability, or resistance to fermentation may be enough to prevent the trans ‐10 shift in beef, leading to rumen conditions similar to those found when feeding conventional corn‐based diets (Duckett et al, 2002) or corn‐based diets supplemented with corn DDGS (Segers et al, 2011).…”
Section: Trans‐10 Shift Discovery In Beef and Lamb And Inherent Differencesmentioning
confidence: 44%
“…Each peak was identified using pure methyl ester standards (Alltech) on the basis of their retention times. 19 Composition of FA in feed samples was analyzed according to He et al 21 Lipids in feed were recovered by evaporating the ethyl ether. Nonadecanoic acid (19:0) methyl ester (100 µL, 5.96 mg/mL hexane; Nu-Chek Prep, Inc.) was added to the residues as an internal standard.…”
Section: Methodsmentioning
confidence: 99%